A case of laryngopharyngeal reflux: CT characterization in the acute setting - Joe Steinman, PhD; Anna Hwang, MD; Stefanie Lee, MD, FRCPC (Radiology Case Reports)
A case of supraglottic thickening and edema in a patient with laryngopharyngeal reflux (LPR) is presented. Symptoms included odynophagia and dysphagia acutely worse over the past 1 day prior to presentation, with recurrent vomiting and gastroesophageal reflux disease (GERD) over the past week. The patient underwent nasopharyngolaryngoscopy (NPL) and CT imaging to evaluate potential airway compromise or masses. Both CT and NPL demonstrated supraglottic swelling, with CT further revealing esophageal wall thickening and inflammation. CT findings of LPR are uncommonly reported, since diagnosis of LPR is typically based on clinical symptoms, direct observation (laryngoscopy), and reflux testing. LPR may be considered as part of the differential for laryngeal edema in the appropriate clinical setting, and awareness of this condition will aid in assessment for related imaging findings.